Heavy Metals and Essential Elements in Association with Oxidative Stress in Women with Polycystic Ovary Syndrome-A Systematic Review - Tinkara Srnovršnik; Irma Virant-Klun; Bojana Pinter (MDPI AG, 2023)
Altered levels of heavy metals and essential elements have been associated with oxidative stress (OS) and metabolic and hormonal changes in women with polycystic ovary syndrome (PCOS). We aimed to summarize the knowledge on the association of heavy metals and essential elements with OS in PCOS. An electronic literature search using PubMed for studies published between January 2008 and April 2023 was conducted. We evaluated heavy metals and essential elements in relation to OS in PCOS in 15 articles. PCOS women had increased antimonium (Sb), cadmium (Cd), lead (Pb), mercury (Hg), arsenic (As), tellurium (Te), thallium (Tl) and osmium (Os) blood levels and decreased zinc (Zn) blood levels; the results of copper (Cu) blood levels were conflicting. Some studies showed a significant correlation between heavy metals (Sb, Cd, Pb, Hg, As, Te and Tl) and essential elements (Se, Zn, Cr, Ca, Mg and Cu) and markers of OS and chronic inflammation. Heavy metals (Sb, Cd, Pb and Hg) and essential elements (Zn, Cr, Se, Ca, Mg and Cu) were associated with metabolic and hormonal characteristics in PCOS. There might be a possible benefit from supplementation therapy in reducing OS and endocrinological problems related to PCOS. Our review confirmed an association between heavy metals and essential elements with OS in PCOS women. This systematic review is registered in PROSPERO under number CRD42023418453.